PENYELENGGARAAN FESTIVAL SIAK BERMADAH DI KABUPATEN SIAK PROVINSI RIAU - Bediona, Zahratul Aini; Sidiq, Rd. Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the organization of The Siak Bermadah Festival in Siak, Riau Province. The research covers the processes of planning, deliberation, socialization, execution, evaluation, and promotion. This research uses a qualitative method with a descriptive approach to elaborate and explain findings derived from data collection through observation and field interviews. The key informants in this study included the Head of The Siak Tourism Office, the Siak Malayu Culture Board, members of Siak Bermadah Festival Organizing Committee, representatives of Traditional Institutions, Festival Participant, and Visitors of The Siak Bermadah Festival. The result indicates that the planning and execution of the festival align with its objectives, namely the preservation of the Malay culture, to attract tourist to visit Siak Regency, and to stimulate the local economic growth. Despite encountering challenges in promotion, budgeting, and coordination, these obstacles are mitigated through ongoing evaluation and continuous improvement efforts. Keyword: Organization, Objectives, Siak Bermadah Festival